Local labor markets and higher education mismatch: What is the role of public and private institutions? - Elena Arias Ortiz; Mary Kaltenberg; Cristian Jara-Figueroa; Ivan Bornacelly; Dominik Hartmann (Inter-American Development Bank (IDB), 2020)
We analyze mismatches between local labor markets and higher education enrollments in 22 educational fields across 137 mesoregions in Brazil between 2009 and 2016 using a two-stage regression model. Local labor markets have a significant effect on enrollment rates by field in higher education institutions and need to be considered by educational policies to prevent skill mismatches. Moreover, a large share of public universities, urban population and low unemployment rates are associated with low mismatches. Public universities address skills shortages, particularly in poor regions and natural sciences, better than private universities that contribute to oversupply, e.g. in business or law.
Keywords: R12; I23; H52; J24; 330; local labor markets; higher education; skills mismatch; public and private institutions